2009
DOI: 10.4149/neo_2009_04_29
|View full text |Cite
|
Sign up to set email alerts
|

Soluble form of carbonic anhydrase IX (CAIX) in transitional cell carcinoma of urinary tract

Abstract: We investigated the expression of cell-associated CAIX protein in histological sections of the transitional cell carcinoma (TCC) of the urinary tract and of the soluble form of CAIX (s-CAIX) shed by the tumor into the serum and urine of TCC patients. A total of 23 patients with histologically confirmed TCC or squamous cell carcinoma (SCC) were enrolled in the pilot study. Sixteen healthy individuals served as controls. Membrane-bound CAIX was present in the tumor cells near the endoluminal surface. Necrosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
(15 reference statements)
4
23
1
Order By: Relevance
“…The sensitivity, specificity, and positive and This study shows that urinary CAIX can serve as a diagnostic marker for UBC. Our results are in line with our previous immunohistochemical study [5] and two small studies on urine samples [6,7]. We were also able to show that detection of CAIX within tumor samples is strongly associated with detection of CAIX in the urine.…”
Section: Introductionsupporting
confidence: 95%
“…The sensitivity, specificity, and positive and This study shows that urinary CAIX can serve as a diagnostic marker for UBC. Our results are in line with our previous immunohistochemical study [5] and two small studies on urine samples [6,7]. We were also able to show that detection of CAIX within tumor samples is strongly associated with detection of CAIX in the urine.…”
Section: Introductionsupporting
confidence: 95%
“…Nevertheless, we showed that the plasma CAIX detected in patients with NSCLC is much lower than CAIX concentrations described in renal cell carcinoma, because the very high constitutive HIF-1a levels in these latter tumours and also differences in CAIX expression depending on the cell type (Li et al, 2008). Increased levels of plasma CAIX have been reported only in urological cancers (Zavada et al, 2003;Li et al, 2008;Hyrsl et al, 2009). Thus, our report is the first study to show evidence of high CAIX levels in the plasma of NSCLC patients.…”
Section: Discussionmentioning
confidence: 51%
“…CAIX is a multidomain protein consisting in an N-terminal proteoglycan-like (PG) domain, an extracellular catalytic domain (CA), a transmembrane segment (TM) and a C-terminal intracytoplasmic (IC) tail (Hilvo et al, 2008). Recent reports have provided evidence that the extracellular domain of CAIX can be released into body fluids of patients with kidney or bladder cancers and a high CAIX plasma level was associated with poor prognosis in these patients (Zavada et al, 2003;Hyrsl et al, 2009). However, the CAIX plasma level has not yet been evaluated in patients with NSCLC.…”
mentioning
confidence: 99%
“…As described in many previous reports, the expression of CA9 has been identified in a large number of human tumors but not in the corresponding normal tissue (67)(68)(69)(70)(71)(72). Moreover, many investigators have reported a high CA9 correlation with a poor prognosis in patients with various tissue-derived carcinomas (69,(73)(74)(75)(76)(77), because hypoxia and acidosis lead to genomic instability, which potentiates further tumor progression. In contrast to CA9 protein expression under hypoxia in the living body, in vitro regulation of the protein expression is reported to be positively related to dense culture (78,79).…”
Section: Increased Expression Of Ca9 In Cultured Cells Under 3dmentioning
confidence: 93%